(untitled) (Physical Education, Health and Social Sciences, 2025)
This study aims to find out the relationship of temporomandibular disorder with vestibular insufficiency. To Study the relationship of ear and balance symptoms in TMD patients such as headache, dizziness, aural fullness, tinnitus, facial pain, postural sway and dysfunction. To evaluate that the association of these two variables (if positive) have any impact on the quality of life of patients with dizziness. A cross-sectional study was conducted on the sample of 126 students of different university population. Individuals of age 18 to 27 years were included who have temporomandibular disorder symptoms and individuals with any systemic disease or trauma were excluded. Fonseca’s questionnaire was used to assess the temporomandibular disorder and then two tests were performed. The one-minute full open mouth test to evaluate the degree of temporomandibular dysfunction either it is mild moderate or severe and stabile-metric test to evaluate the relationship of temporomandibular dysfunction with vestibular insufficiency. Then to analyze the study by SPSS, chi-square was applied. Results showed that p<0.05, value of p is less than value of α so that means null hypothesis is rejected and alternate hypothesis is proved. There is strong association between temporomandibular disorder and vestibular insufficiency but usually people ignore their symptoms due to lack of awareness.